لێكەوتەكانى لەكە لە كەسێتى خوێندكار : توێژینەوەیەكى مەیدانییە لە خوێندنگە ئامادەییەكانى شاری سلێمانى - محمد, پ.ی.د.كەژال حسین; حمەرشید, بەختیار غفور (Sulaimani Journal for Humanities, 2023)
The Outcome (Labeling-stigma) of Insult on Student Personality is field research in the high schools of Sulaimani, Kurdistan Region of Iraq. This research sheds light on name-calling that is said to students by themselves and others. The aim of this study is to find out the social and psychological outcomes of this on student personality in the high schools of Sulaimani. The study is a descriptive-analytical research method used is qualitative and quantitative. The researcher has conducted interviews with the social instructors in the schools and has given students an inventory to collect data. The participants are 10th and 11th-grade high school students in Sulaimani. There are (176) students. Two kinds of samples have been used (Intentional improbable) which is used with the social instructors and the other is (Snowballs) Which is used with the students. The study results indicate that students who have been called names or insulted are socially disturbed, have a bad reputation, have weaker relationships, and have less class participation. The psychological outcomes include personality disorder, feeling ashamed of themselves, fear of peers, anxiety, low self-esteem, and depending on others. The more social and psychological outcomes increase, the more extreme the insulted student would react, hence, the impact of insult on the student’s personality increases.
Keywords: stigma; social stigma; personality; student